Closed-chest occlusion of the left anterior descending artery in swine infarction model: Review - Kőrösi, Dénes; Vorobcsuk, András; Fajtai, Dániel; Tátrai, Ottó; Bodor, Emőke; Garamvölgyi, Rita (Acta Agraria Kaposváriensis, 2024)
Pigs have played a significant role in biological and medical research for many years. In the case of non-rodent models, pigs are the primary choices as experimental animals in the cardiovascular studies. Accumulating data indicate that the closed-chest coronary balloon-occlusion technique is one of the most successful method for creating ischemic heart failure (HF). However, consistent and thoroughly characterized large animal models of HF are a critical translational tool for drug development and toxicology. The knowledge of the different catheterization protocols is crucial to ensure a suitable animal model which can serve as a human-related preclinical validation process. Therefore it is essential to follow an optimized and standardized experimental protocol on a homogenous animal population, which help to obtain reliable and useful data for the translational large animal research programs.
Keywords: myocardial infarction in pigs; translational research; coronary occlusion; large animal modeling